Library management for the digital age a new paradigm - Todaro, Julie 1950- (Lanham Rowman & Littlefield, 2014)
"This updated edition of the renowned library management textbook provides a comprehensive overview of the techniques needed to effectively manage a contemporary library or information center"--Provided by publisher.
First through third editions, published 1977-1987, have title Library management; Fourth through seventh editions, authored by Robert D. Stueart and Barbara B. Moran and published 1993-2007, have title Library and information center management
Includes bibliographical references and index.
Keywords: Library administration; Library administration -- Case studies